Say the right thing : how to talk about identity, diversity, and justice - Yoshino, Kenji (Atria Books, 2023)
"In the current period of social and political unrest, conversations about identity are becoming more frequent and more difficult. On subjects like critical race theory, gender equity in the workplace, and LGBTQ-inclusive classrooms, many of us are understandably fearful of saying the wrong thing. That fear can sometimes prevent us from speaking up at all, depriving people from marginalized groups of support and stalling progress toward a more just and inclusive society. Kenji Yoshino and David Glasgow, founders of the Meltzer Center for Diversity, Inclusion, and Belonging at NYU School of Law, are here to show potential allies that these conversations don't have to be so overwhelming. Through stories drawn from contexts as varied as social media posts, dinner party conversations, and workplace disputes, they offer seven user-friendly principles that teach skills such as how to avoid common conversational pitfalls, engage in respectful disagreement, offer authentic apologies, and better support people in our lives who experience bias. Research-backed, accessible, and uplifting, Say the Right Thing charts a pathway out of cancel culture toward more meaningful and empathetic dialogue on issues of identity. It also gives us the practical tools to do good in our spheres of influence. Whether managing diverse teams at work, navigating issues of inclusion at college, or challenging biased comments at a family barbecue, Yoshino and Glasgow help us move from unconsciously hurting people to consciously helping them"--